P-029 a prospective multi-center trial of transform™ occlusion balloon catheter (tobc): trial design and results. (26th July 2015) - Taqi, M; Quadri, S; Puri, A; Fitzsimmons, B; Rai, A; Given, C; Masso, J; Powers, C; English, J; Zaidat, S
Abstract : Background: Wide-necked and large intracranial aneurysms are challenging to treat through endovascular approach. Adjunctive treatments like Balloon-assisted coil embolization (BACE) and Stent-assisted coil embolization (SACE) play a major role in the treatment of such aneurysms. The TransForm™ Occlusion Balloon Catheter (TOBC) registry is intended to evaluate safety and  efficacy of BACE using the TOBC. It is the first prospective registry trial of BACE for intracranial aneurysms. Hypothesis: BACE using TOBC is safe and effective. Design: The TOBC registry is a prospective multicenter registry trial. 7 sites in the USA and 1 in Spain were selected to enroll; each site could enroll up to 20 patients. Final analysis of data collected for 81 patients enrolled from November 2013 through January 2015 was performed. Results: Mean age was 54.78 yrs (SD±14.51). 30.86% were male and 69.14% were females. TOBC was used for BACE in 73.9%, test occlusion 5.7%, safety 9.1% and others (vasospasm and post flow diverter placement) 11.4%. Most common arteries where TOBC was used were internal carotid artery (35.9%), MCA (18.5%), ACA (13.0%) and BA (10.9%). Mean proximal vessel diameter was 3.29 mm (SD±1.19). Mean distal vessel diameter was 2.89 mm (SD±1.26). Most common contrast concentrations used were 70/30 (35.87%) and 50/50 (30.43%). Most common balloon type used were Compliant 4 x 10 mm (31.40%) and Super compliant 4 x 7 mm (17.44%). Most common guide wires used were Transend (54.9%) and Synchro14 (15.9%). Mean dome to neck ratio of the aneurysms treated was 1.31 (SD±0.69). 50% were at bifurcation, 45.8% of the aneurysms were sidewall and 4.17% were terminal aneurysms. Following were the means scores (1= Excellent, 2=Very good, 3=Good, 4= Fair, 5=poor); for visibility under fluoroscopy 1.78 (SD±0.84), ability to reach intended site 1.59 (SD±0.78), stability during first positioning 1.54 (SD±0.63), stability during inflation 1.56 (SD±0.68), stability during deflation 1.57 (SD±0.64), ability to temporarily stop flow 1.55 (SD±0.67), ability to assist in coil embolization 1.71 (SD±0.80). Mean time to inflate the balloon was 4.85 seconds (SD±3.17) and mean time to deflate was 5.64 seconds (SD±4.53). Complete obliteration of the aneurysm (Raymond class I) was achieved in 69.44%. Thrombus formation occurred in 4/81 (4.8%) cases. In all cases thrombus resolved with medications and no patient suffered infarction. In all cases an underlying hyper coagulable state from subarachnoid hemorrhage was considered a contributing factor. Vessel rupture/perforation occurred in 1/81 (1.2%) case but was unrelated to TOBC. Conclusions: BACE using TOBC was safe and effective. The balloon catheter performed as intended in the treatment of cerebral aneurysms in our cohort of patients. All variables assessed for TOBC performance showed good to excellent results. No serious side effects occurred. The short inflation and deflation times and ability to use a 0.014 guidewire allowed improved performance of this balloon catheter in comparison to older balloon catheters available. Disclosures: M. Taqi: None. S. Quadri: None. A. Puri: None. B. Fitzsimmons: None. A. Rai: None. C. Given: None. J. Masso: None. C. Powers: None. J. English: None. S. Zaidat: None.